Hubungan Teman Sebaya Terhadap Perilaku Menyimpang Siswa di SMP Bang Saller Liwubao Kecamatan Hewokloang - Gradiana Guru; Abdullah Muis Kasim; Gustav Gisela Nuwa (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study aims to find peer relations with students' deviant behavior and factors that cause deviant behavior of students at Muhammadiyah Middle School Waipare. This research was conducted for one month starting from June 1 until June 30, 2022, the research method used was descriptive method with a qualitative approach. Data collection techniques through observation, interviews and documentation. The results showed that there was a peer relationship with students' deviant behavior. One of the factors that caused this was that there was an influence from relationships with peers who were not good. Therefore, the results of this study can be concluded that there is a peer relationship to the occurrence of deviant behavior of students at Bang Saller Middle School Liwubao.